Tecnostress in higher education students: An exploratory study - Yener, S.; Belchior-Rocha, H.; Arslan, A. (EDULEARN24 Proceedings, 2024)
The ubiquitous presence of technology in daily life brings both beneficial and detrimental consequences, with technostress emerging as a significant concern characterized by stress induced by technology use. Symptoms encompass physical, psychological, and behavioral aspects. Given that university students are constantly engaged in information-seeking activities and interacting with various individuals, it is imperative to identify technostress symptoms and assess their perceptions of technology use. This research aims to propose interventions tailored to the reality and needs of students. A semi-structured interview approach was employed with a sample of 120 university students, drawn from a public university. Participants were first asked about their feelings regarding technology use, followed by a questionnaire comprising 27 physical, psychological, and behavioral technostress symptoms. Participants indicated symptoms experienced over the past year. The top three reported symptoms were “Anxiety”, “Stress” and “Mental fatigue”. Furthermore, 55.55% of participants expressed feelings of addiction/dependence or excessive time spent on electronic devices, pervasive across various life domains. These findings underscore the need for further investigation into the extent of technostress among university students, with implications for the development of targeted interventions to mitigate its adverse effects.